2016
DOI: 10.1590/2358-2936e2016025
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in biomass and size of seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) (Decapoda: Penaeoidea) on the southern coast of São Paulo state, Brazil

Abstract: Xiphopenaeus kroyeri (Heller, 1862) is the third most common species caught by fi shing boats in the state of São Paulo, Brazil and production of this shrimp in the Cananéia region located on the southern coast of this state ranks second in the nation. Th e aim of this study was to investigate the temporal variation of the total biomass and size of X. kroyeri and analyze this variation against environmental factors in order to suggest some information about the best periods to fi sh this species. Samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The offseason shrimp fishery, from March 1st until May 31th (IBAMA, 2008), is the only protection strategy that aims to reduce fishing pressure in the Southeast and Southern Brazilian regions. Previous studies have indicated that the offseason period has also benefited seabob shrimp (Heckler et al, ,2013, 2014; Miazaki et al, 2016). However, the offseason period in the Southeastern and Southern regions was designed to protect juvenile pink shrimp ( Farfantepenaeus spp.)…”
Section: Discussionmentioning
confidence: 95%
“…The offseason shrimp fishery, from March 1st until May 31th (IBAMA, 2008), is the only protection strategy that aims to reduce fishing pressure in the Southeast and Southern Brazilian regions. Previous studies have indicated that the offseason period has also benefited seabob shrimp (Heckler et al, ,2013, 2014; Miazaki et al, 2016). However, the offseason period in the Southeastern and Southern regions was designed to protect juvenile pink shrimp ( Farfantepenaeus spp.)…”
Section: Discussionmentioning
confidence: 95%
“…The closed season has provided favourable results in some regions of Brazil. According to studies carried out in the Cananéia region, as well as Babitonga Bay (Santa Catarina state, 26°S) and Santos Bay (São Paulo state, 24°S), the highest abundance of juvenile and reproductive females of Xiphopenaeus kroyeri (Heller, 1862) coincided with months when fishing is prohibited (Heckler et al ., 2013; Grabowski et al ., 2016; Miazaki et al ., 2016). Thus, these individuals are not being captured during this period, favouring the maintenance of the population stock.…”
Section: Introductionmentioning
confidence: 99%
“…Pôde ser observado, através dos mapas da distribuição da CPUE estimada por krigagem e do gráfico da CPUE média dentro das diferentes áreas, que nos anos de 2009 e 2010 a abundância da espécie foi semelhante entre as áreas de despejo da dragagem e de fundeio de embarcações, enquanto nos anos de O camarão-sete-barbas é uma espécie que possui como áreas preferenciais locais com sedimentos finos e ricos em fragmentos vegetais (COSTA et al, 2007, HECKLER et al, 2014MIAZAKI et al, 2016). Assim, regiões costeiras próximas a desembocaduras de estuários, como a área marinha costeira ao largo do porto de Santos, são consideradas habitat preferenciais para alimentação e crescimento da espécie (CASTRO et al, 2005, NAKAGAKI;NEGREIROS-FRANSOZO, 1998).…”
Section: Correlações-cruzadas Entre Os Dados Pesqueiros E Estatísticounclassified